1996
DOI: 10.1111/j.1751-1097.1996.tb01856.x
|View full text |Cite
|
Sign up to set email alerts
|

EPR Detection of Free Radicals in UV‐lrradiated Skin: Mouse Versus Human

Abstract: Ultraviolet radiation produces free radicals in Skh-1 mouse skin, contributing to photoaging and carcinogenesis. If a mouse model is a general indicator of free radical processes in human skin photobiology, then radical production observed in mouse and human skin should be directly comparative. In this work we show that UV radiation (A > 300 nm, 14 pW/cmZ W B ; 3.5 mW/cmz UVA) increases the ascorbate free radical (Ax'-) electron paramagnetic resonance (EPR) signal in both Skh-1 mouse skin (45%) and human facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 24 publications
5
87
0
Order By: Relevance
“…All images are displayed using the same intensity scale, in which regions of bright red and yellow indicate high fluorescence signal. R-123 fluorescence was predominately detected from the cytoplasm of the keratinocytes of each epidermal layer, which is consistent with data collected previously on Epiderm and ex vivo tissues and is attributed to ROS generation from intrinsic chromophores (i.e., NADH, riboflavin, mitochondria) [19,20,[29][30][31]. Regions of dark blue in the nuclei and extracellular spaces indicate low fluorescence signal equivalent to typical autofluorescence levels as displayed in Figs.…”
Section: Resultssupporting
confidence: 89%
“…All images are displayed using the same intensity scale, in which regions of bright red and yellow indicate high fluorescence signal. R-123 fluorescence was predominately detected from the cytoplasm of the keratinocytes of each epidermal layer, which is consistent with data collected previously on Epiderm and ex vivo tissues and is attributed to ROS generation from intrinsic chromophores (i.e., NADH, riboflavin, mitochondria) [19,20,[29][30][31]. Regions of dark blue in the nuclei and extracellular spaces indicate low fluorescence signal equivalent to typical autofluorescence levels as displayed in Figs.…”
Section: Resultssupporting
confidence: 89%
“…Increase of signal intensity, measured as height of signal amplitude of cw EPR measurements, indicates that during irradiation free radical oxidative stress occurs [35,36]. However, Haywood et al showed that a significant increase of ascorbate radical concentration is detectable during irradiation only.…”
Section: Direct Detection Of Uv Generated Radicals In Skinmentioning
confidence: 99%
“…The use of spin traps is the most frequently applied method for this purpose [18,36,38]. It involves the reaction of a free radical with a diamagnetic trapping compound resulting in a longer living, EPR detectable species.…”
Section: Stabilising Short-lived Radicalsmentioning
confidence: 99%
“…Due to the range of reactions DHA must undergo to become melanoidin, it could form free radical intermediates that could prove toxic to the skin (Wiseman & Halliwell, 1996;Thorpe & Baynes, 2003). If spray tan users are consistently exposed to sunlight without the protection of sunscreen, then free radicals could form with the help of DHA as UV light has been documented to produce free radicals in direct exposure to skin (Jurkiewicz & Buettnerf, 1996). This paper aims to determine whether dihydroxyacetone is capable of presenting any significant risk of toxicity in humans when exposed to ultraviolet radiation by investigating current toxicological studies and data performed on DHA activity.…”
Section: Introductionmentioning
confidence: 99%